2005
DOI: 10.1093/geront/45.2.231
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' Perspectives on Caring for Cognitively Impaired Elders

Abstract: Profound changes occur in the process of care with cognitively impaired patients. The increased complexity mandates an expanded model of care that addresses the prominent psychosocial and ethical aspects of care as well as the medical ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 18 publications
2
30
0
5
Order By: Relevance
“…Dementia creates acute and intensive demands because of its behavioral complexity, chronicity, the patients' growing dependence on and involvement of informal helpers and family members, and the presence of comorbid health problems that compete for the attention of providers. Our findings are consistent with prior work on physician views of issues in early diagnosis and management 23,32 and 1 study examining longer term issues in dementia care 27 . Dementia often starts as a problem with cognition, but it almost always evolves into a problem with behavior.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Dementia creates acute and intensive demands because of its behavioral complexity, chronicity, the patients' growing dependence on and involvement of informal helpers and family members, and the presence of comorbid health problems that compete for the attention of providers. Our findings are consistent with prior work on physician views of issues in early diagnosis and management 23,32 and 1 study examining longer term issues in dementia care 27 . Dementia often starts as a problem with cognition, but it almost always evolves into a problem with behavior.…”
Section: Discussionsupporting
confidence: 89%
“…25,26 Health care systems issues, particularly insufficient time, are often mentioned as barriers to diagnosis or management. 23,25 Whereas most studies focus on the initial assessment and management, Adams and colleagues 27 describe challenges primary care physicians face in the ongoing care of persons with dementia, including a shift from curing to caring, increasing reliance on the family, and ethical dilemmas. In discussing their findings, they note that dementia does not "fit well" within many physician's practice settings.…”
Section: Introductionmentioning
confidence: 99%
“…27 Research indicates that other dilemmas related to disclosure arise for GPs: anxieties about how persons may cope coming to terms with a progressive disability; 2 and ethical issues as medical decisions move from the patient to someone else. 28 The literature supports these GP concerns for patient wellbeing. While Pinner and Bouman's clinic sample had no major incidents following disclosure to patients, after 1 year 6% required antidepressant treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Although several studies have shown that mild to moderately impaired patients with dementia can provide reliable self-report information about their health and well-being (6, 9-11), family members are frequently viewed as the primary source of patient status information (12). Unfortunately, agreement between patient and caregiver reports of patient status is low to moderate at best (6, 7, 9-11, 13), raising questions about the usefulness of family proxy reports as guides to patient treatment.…”
Section: Introductionmentioning
confidence: 99%